Analisis Strategi Persaingan Usaha Pada UD. Berkah Anugrah Dalam Meningkatkan Pendapatan - Asror, Khozinatul; Amri, Muhtadin (Universitas Labuhanbatu, 2024)
Business competition is a common problem in the business world. By implementing various strategies to deal with competition so that it creates a significant impact on the business unit to face business competition in increasing revenue. The main objective of this research is to analyze the business competition strategy in dealing with the business competition implemented by UD. Berkah Anugrah, considering that the competition in a similar business is so tight in the surrounding environment. This type of research uses field research , in which data search and data collection is carried out by researchers who are directly present in the field. While this research uses a qualitative descriptive approach, which focuses on problem solving. This study uses interview and observation data collection techniques. Interviews and observations were conducted with UD owners, employees and consumers. Blessing of Anugrah Bangunsari Ponorogo. The results of this study indicate that UD. Blessing Anugrah Bangunsari Ponorogo has implemented a strategy in dealing with business competition that aims to win business competition so that it has a good impact on UD. Blessings of Grace. From this strategy implemented well by UD. Blessings of Anugrah, even though there are some obstacles, these obstacles can be overcome. So that with the implementation of the maximum strategy by UD. Thanks to Anugrah and its employees, UD. Berkah Anugrah obtains maximum results in the face of competition with its competitors.